2021
DOI: 10.1177/1045389x211011671
|View full text |Cite
|
Sign up to set email alerts
|

PH-sensitive hydrogel-based valves: A transient fully-coupled fluid-solid interaction study

Abstract: pH-sensitive hydrogels are promising materials to be employed in microfluidic devices, especially microvalves. In this paper, a theory of transient swelling of pH-sensitive micro-valve is presented. A transient constitutive model that captures electrical, chemical, and mechanical fields is considered to model the swelling phenomenon. The diffusion of ions into the hydrogel, the electromigration, and convection are described by implementing the Nernst-Planck equation. Assuming Gent model, hydrogel is considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In recent years, the researchers found that the actuate membrane materials including sodium alginate [8] , cellulose, chitosan [9][10][11][12] . Due to their unique three-dimensional network structure and ability to retain a large amount of water, ion actuator had a wide range of applications in hydrogel arti cial muscles [13] including biomedical applications, drug carriers [14][15] , biosensors [16] , medical devices [17] , tissue engineering [18] , separation systems [19][20] , micro uidic systems [21] , microvalves [22] and actuator [23][24] . Chitosan (CS) was a product of natural chitin.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the researchers found that the actuate membrane materials including sodium alginate [8] , cellulose, chitosan [9][10][11][12] . Due to their unique three-dimensional network structure and ability to retain a large amount of water, ion actuator had a wide range of applications in hydrogel arti cial muscles [13] including biomedical applications, drug carriers [14][15] , biosensors [16] , medical devices [17] , tissue engineering [18] , separation systems [19][20] , micro uidic systems [21] , microvalves [22] and actuator [23][24] . Chitosan (CS) was a product of natural chitin.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the swelling and de-swelling of hydrogels, these materials undergo considerable volume change under a change in external stimuli, including temperature, pH, light intensity, ion concentration, electric and magnetic fields (Kasinathan and Srinivasan, 2018;Shojaeifard and Baghani, 2019;Shojaeifard et al, 2019aShojaeifard et al, , 2019bShojaeifard et al, , 2021. Although conventional hydrogels have various merits to be utilized in diverse applications (Bin et al, 2021;Guenther et al, 2009;Niroumandi et al, 2021bNiroumandi et al, , 2022, the composition of inhomogeneous networks and low polymer content make the hydrogels mechanically weak. Moreover, regarding the enthusiasm for finding alternatives for living tissue, researchers seek a biocompatible material that can absorb water and possess high toughness and shock absorption.…”
Section: Introductionmentioning
confidence: 99%